Production of cotton seeds in the scope of agribusiness (Research, Society and Development, 2022)
The production of cotton seeds in Brazil is expanding every year aiming, above all, to attend to the expansion of the cultivated area in the Center-West region. In a general way, the route followed by the seeds from the field to the factory consists of harvesting, transportation, processing in sawmills, as well as clear processes carried out in the seeds, such as: delinting, pre-cleaning and classification, treatment, packaging and storage at the next seed. The objective of this study was to gather information and present it so that they can assist in decision making in the production of cotton seeds in the context of agribusiness. For this purpose, a narrative review was chosen, which was carried out through searches of bibliographic references in the different indexing bases (Portal of CAPES periodicals, Google academic and Scielo), and also in the references of the studies selected to compose this article, always looking for topics related to the culture studied. Thus, in this study, a series of quality control measures was observed that is required during any of the phases of the production process, whose main objective is to prevent the seeds from suffering genetic or varietal contamination and also mechanical damage, since the use of high quality seeds can prevent problems in labor and financial prejudices resulting from irregularities and failures in the emergency. Failures in cotton in various producing regions of the country are frequent, mainly due to the use of seeds of unknown origin and quality.